2/3 (x - 4) = 2x.

Question

Asked 10/9/2013 5:40:30 AM

Updated 1/14/2015 11:21:56 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [1/14/2015 11:21:16 PM]

scorpionsheep|Points 90|

scorpionsheep|Points 90|

scorpionsheep|Points 90|

Question

Asked 10/9/2013 5:40:30 AM

Updated 1/14/2015 11:21:56 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [1/14/2015 11:21:16 PM]

Rating

3

2/3 (x - 4) = 2x

2(x - 4) = 2x(3)

2x - 8 = 6x

2x - 6x = 8

-4x = 8

x = -2

2(x - 4) = 2x(3)

2x - 8 = 6x

2x - 6x = 8

-4x = 8

x = -2

Added 1/14/2015 11:21:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/14/2015 11:31:36 PM]

27,097,174

questions answered

There are no comments.